One potato, two potato - DeFelice, Cynthia C. (Farrar Straus Giroux, 2006)
This retelling of a Chinese folktale pays tribute to the author's Irish heritage, and to the joys of an old marriage, new friendships, and the impulse to share. Using pen and gouache, the artist shows the "simple" characters in all their winning complexity. A very poor, humble couple live so simple a life they share everything, until the husband discovers a pot with magical powers buried under the very last potato in the garden. Mr. and Mrs. O'Grady are so poor they have just one of everything to share - one potato a day, one chair, one blanket full of holes, and one gold coin for a rainy day. After digging up the last potato in their patch, Mr. O'Grady comes upon a big black object. It's a pot - no ordinary pot, for what they soon discover is that whatever goes into it comes out doubled! Suddenly the O'Gradys aren't destitute anymore. But what they really long for is one friend apiece. Can the magic pot give them that?